2019
DOI: 10.1002/2211-5463.12626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative nuclear localization signal in the tumor suppressor maspin sheds light on its nuclear import regulation

Abstract: The tumor suppressor activity of maspin (mammary serine protease inhibitor) has been associated with its nuclear localization. In this study we explore the regulation of maspin nuclear translocation. An in vitro nuclear import assay suggested that maspin can passively enter the nucleus. However, in silico analysis identified a putative maspin nuclear localization signal ( NLS ), which was able to mediate the nuclear translocation of a chimeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…26 Furthermore, Reina et al reported that the transport of maspin from the cytoplasm to the nucleus involves a 28-amino acid sequence within the maspin protein and three-dimensional regulation of protein structure. 27 These findings may help explain our observations, which indicated that the mechanism regulating the subcellular localization of maspin is disrupted in RERF-LC-KJ cells. However, since the detailed molecular mechanisms of nuclear translocation of maspin have not yet been elucidated, further investigations are required to clarify this finding.…”
Section: Discussionsupporting
confidence: 69%
“…26 Furthermore, Reina et al reported that the transport of maspin from the cytoplasm to the nucleus involves a 28-amino acid sequence within the maspin protein and three-dimensional regulation of protein structure. 27 These findings may help explain our observations, which indicated that the mechanism regulating the subcellular localization of maspin is disrupted in RERF-LC-KJ cells. However, since the detailed molecular mechanisms of nuclear translocation of maspin have not yet been elucidated, further investigations are required to clarify this finding.…”
Section: Discussionsupporting
confidence: 69%
“…Alternatively, Reina et al . reported that the sequence of 28 amino acids in maspin protein (KLIKRLYVDKSLNLSTEFI-SSTKRPYAK) acts as a NLS and speculated that the nuclear-cytoplasmic transport of maspin may be controlled through the regulation of its three-dimensional conformation 43 . Although these reports help us in understanding the mechanisms underlying subcellular translocation of maspin, the exact details of this process remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, maspin residues from 87-114 were proposed to harbor nuclear localization signal, and their exposure impact maspin localization (Reina et al ., 2019). When the exposure has been calculated for the entire length, maspin-S176 showed slightly higher solvent accessibility than maspin-P176, however, for 87-94 (s2A), maspin-S176 was significantly higher referring to the higher possibility of this variant being nuclear-localized (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%